AGROCHEMICAL PROPERTIES OF TYPICAL GRAY SOILS OF THE FERGANA REGION, OLDLY IRRIGATED (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article examines and studies the agrochemical properties of typical irrigated gray soils of the Fergana Valley, namely humus, amino acids, total nitrogen, phosphorus, potassium, and the granulometric composition of the soils.